Membrane electrode heat treatment method for changing catalyst layer ionomer cluster and application thereof
By coating the catalyst on the surface of the proton exchange membrane and performing heat treatment, the problem of uneven ionomer distribution in the catalytic layer is solved, the proton conduction efficiency is improved, the operating cost of the fuel cell is reduced, and the electrolytic performance is improved.
Patent Information
- Application Number
- CN202411249508.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The ionomer distribution in the existing catalytic layer is uneven, resulting in low proton conduction efficiency, affecting the performance and cost of fuel cells.
A membrane electrode heat treatment method is adopted to change the ionomer cluster of the catalytic layer, including coating the catalyst on the surface of the proton exchange membrane and performing heat treatment, the heat treatment temperature is 150-250°C, the time is 1-3 hours, and further acid treatment is carried out to Ensure that the membrane electrode is completely protonated.
The mobility of ionomers in the catalytic layer is improved, the ohmic loss is reduced, the overall electrolytic performance of the membrane electrode is improved, the use of precious metal catalysts is reduced, and the operating cost of fuel cells is reduced.
Smart Images

Figure CN119133473A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membrane fuel cells, and in particular relates to a membrane electrode heat treatment method for changing ionomer clusters in a catalytic layer and an application thereof. Background Art
[0002] As a key component of PEM electrolyzer / fuel cell, membrane electrode is one of the key determinants of the cost and performance of PEM electrolyzer / fuel cell. The catalyst layer is the main site of the reaction. The ionomer in the catalyst layer wraps the catalyst particles and acts as a proton conductor and binder. The ionomer is a polymer composed of repeating units of electrically neutral units and ionized units. By complexing metal ions into the polymer matrix, the strength and toughness of the ionomer system are increased.
[0003] Some applications that use ionomers to increase the toughness of the entire system include coatings, adhesives, impact modifiers, and thermoplastics. Aggregation in the catalyst ink affects a series of issues such as proton transfer, gas transport, and electron transfer. Efficient ionomers in the catalyst layer should have the following characteristics: high proton conductivity, high gas / water permeability, and high stability. However, since the distribution of ionomers in the catalyst layer is not completely uniform, its proton conduction efficiency needs to be improved. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the main purpose of the present invention is to provide a membrane electrode heat treatment method for changing the ionomer clusters in the catalytic layer, aiming to solve the problem of poor conductivity of existing catalysts. The purpose of the present invention is also to provide an application of the membrane electrode heat treatment method.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A membrane electrode heat treatment method for changing ionomer clusters in a catalyst layer comprises the following steps:
[0007] 1) Coating a catalyst on the surface of a proton exchange membrane;
[0008] 2) Heat treating the membrane electrode obtained in step 1).
[0009] In some specific embodiments, the method further comprises subjecting the heat-treated proton exchange membrane to an acid treatment.
[0010] In certain specific embodiments, in step 1), the catalyst is coated on the surface of the proton exchange membrane, specifically, a cathode hydrogen evolution catalyst slurry and an anode hydrogen evolution catalyst slurry are coated on the anode and cathode of the proton exchange membrane, respectively.
[0011] In certain specific embodiments, the cathode hydrogen evolution catalyst slurry comprises Pt / C powder, ionomer solution, solvent and water in a ratio of 15-20 mg: 50-100 mg: 2-8 ml: 3-10 ml.
[0012] In certain specific embodiments, the platinum content in the Pt / C powder is 20-60wt%, the ionomer is a perfluorosulfonic acid resin with a mass concentration of 3-8%, the solvent is n-propanol, and the water is deionized water.
[0013] In certain specific embodiments, the anode hydrogen evolution catalyst slurry comprises IrO2 powder, ionomer solution, solvent and water in a ratio of 30-60 mg: 120-180 mg: 5-15 ml: 2-8 ml.
[0014] In certain specific embodiments, the iridium content in the IrO2 powder is 70-90wt%, the ionomer is a perfluorosulfonic acid resin with a mass concentration of 3-8%, the solvent is n-propanol, and the water is deionized water.
[0015] In some specific embodiments, the membrane electrode is subjected to cation exchange treatment before the membrane electrode is heat treated; and the cation exchange treatment is specifically: the proton exchange membrane is placed in an aqueous solution containing cations and soaked for 10-15 hours, and then washed with deionized water.
[0016] In certain specific embodiments, the heat treatment conditions in step 2) are: heat treatment temperature is 150-250° C., and heat treatment time is 1-3 h.
[0017] In some specific embodiments, the acid treatment in step 3) is: placing the heat-treated membrane electrode in a H2SO4 solution (5wt%) for soaking for multiple times to ensure that the membrane electrode is completely protonated, and after the soaking treatment is completed, rinse it with deionized water and store it.
[0018] The invention discloses an application of the membrane electrode heat treatment method for changing the ionomer clusters of the catalytic layer in water electrolysis for hydrogen production, alkaline water electrolysis, carbon dioxide reduction and fuel cells.
[0019] Compared with the prior art, the present invention has at least the following advantages:
[0020] 1) The membrane electrode heat treatment method provided by the present invention improves the mobility of the main chain and side chain of the ionomer in the catalyst layer to varying degrees by heat treating the membrane electrode, thereby changing the structure of the ionomer clusters in the catalyst layer, reducing the ohmic loss, and improving the overall electrolysis performance of the membrane electrode, thereby reducing the operating costs of the electrolysis of water to produce hydrogen and the operation of the fuel cell;
[0021] 2) In this application, the same catalytic performance can be achieved by using a lower catalyst loading after heat treatment of the membrane electrode. Therefore, in practical applications, the loading of the precious metal catalyst can be reduced, thereby reducing the raw material and depreciation costs of the water electrolysis hydrogen production hybrid fuel cell and improving the overall benefits;
[0022] 3) By heat treating the membrane electrode, it has the advantages of easy processing, high processing efficiency and no change in the catalyst layer structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0024] Figure 1 This is a SEM electron microscope scanning image of the membrane electrode prepared in Example 2 of the present invention;
[0025] Figure 2 The polarization curves of the membrane electrodes prepared in Example 2 and Comparative Examples 1-3 of the present invention;
[0026] Figure 3 This is a diagram showing the thermal stability performance of the membrane electrode prepared in Example 2 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0028] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0029] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0030] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0031] Example 1
[0032] The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer provided by the present invention comprises the following steps:
[0033] S1: Coating a catalyst on the surface of a proton exchange membrane, specifically:
[0034] Wherein, step S1 specifically comprises: placing a proton exchange membrane (commercial Nafion 115) on a vacuum heating plate of an ultrasonic spray coating machine, and spraying the catalyst slurry on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0035] S1.1, cathode spraying hydrogen evolution catalyst slurry;
[0036] S1.2, anode spraying of oxygen evolution catalyst slurry.
[0037] Specifically, step S1.1 includes: the cathode hydrogen evolution catalyst slurry includes Pt / C powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spraying machine after ultrasonic mixing, and sprayed in a serpentine route, and sprayed alternately in the horizontal and vertical directions, and dried after the spraying is completed, and turned over after the drying is completed;
[0038] The platinum content of the Pt / C powder is 25wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 3wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 15mg of Pt / C powder, 50mg of ionomer solution, 2mL of n-propanol and 6mL of deionized water are taken, and the mixed solution is subjected to ice bath ultrasonic treatment for 20 minutes to obtain a Pt / C slurry for the cathode.
[0039] The Pt / C slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed in a serpentine route and alternately in the horizontal and vertical directions, and finally the cathode catalyst loading was 0.2mgPt / cm 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0040] Among them, step S1.2 specifically includes: the anode oxygen evolution catalyst slurry includes IrO2 powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spray machine after ultrasonic mixing, sprayed according to a serpentine route, and sprayed alternately horizontally and vertically, and dried after spraying, and the membrane electrode is obtained after drying.
[0041] Specifically, the iridium content of IrO2 powder is 70wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin (Nafion) concentration of 3wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 30mgIrO2 powder, 120mg Nafion solution, 7mL n-propanol and 3mL deionized water (added in equal amounts twice) are taken and added and mixed in the order of water-IrO2 powder-water-n-propanol-Nafion solution. The mixed solution is ultrasonically treated for 20 minutes to obtain the IrO2 slurry of the anode.
[0042] The IrO2 slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying, and the spraying was carried out alternately in the horizontal and vertical directions. Finally, the anode catalyst loading of 2.0 mg Ir / cm was obtained. 2 After spraying, the membrane electrode was obtained by drying for 30 minutes.
[0043] S2: Perform cation exchange treatment on the sprayed membrane electrode, specifically:
[0044] The proton exchange membrane was placed in a 5 wt % NaCl solution and soaked for 10 h to ionize the proton exchange membrane, and then washed with deionized water.
[0045] S3: Heat treatment of the membrane electrode, specifically:
[0046] The membrane electrode treated with cation exchange was placed in an oven at 150° C. and baked for 3 h to obtain a heat-treated membrane electrode.
[0047] S4: Acid treatment is performed on the heat-treated membrane electrode, specifically:
[0048] The heat-treated membrane electrode is placed in a H2SO4 solution (5wt%) and immersed for 4 times to ensure that the membrane electrode is completely protonated. After the immersion treatment is completed, it is rinsed with deionized water and stored.
[0049] Example 2
[0050] The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer provided by the present invention comprises the following steps:
[0051] S1: Coating a catalyst on the surface of a proton exchange membrane, specifically:
[0052] Wherein, step S1 specifically comprises: placing a proton exchange membrane (commercial Nafion 115) on a vacuum heating plate of an ultrasonic spray coating machine, and spraying the catalyst slurry on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0053] S1.1, cathode spraying hydrogen evolution catalyst slurry;
[0054] S1.2, anode spraying of oxygen evolution catalyst slurry.
[0055] Specifically, step S1.1 includes: the cathode hydrogen evolution catalyst slurry includes Pt / C powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spraying machine after ultrasonic mixing, and sprayed in a serpentine route, and sprayed alternately in the horizontal and vertical directions, and dried after the spraying is completed, and turned over after the drying is completed;
[0056] The platinum content of the Pt / C powder is 40wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 17.4mg of Pt / C powder, 70mg of ionomer solution, 3.4mL of n-propanol and 4.6mL of deionized water are taken, and the mixed solution is subjected to ice bath ultrasonic treatment for 20 minutes to obtain a Pt / C slurry for the cathode.
[0057] The Pt / C slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed in a serpentine route and alternately in the horizontal and vertical directions, and finally the cathode catalyst loading was 0.2mgPt / cm 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0058] Among them, step S1.2 specifically includes: the anode oxygen evolution catalyst slurry includes IrO2 powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spray machine after ultrasonic mixing, sprayed according to a serpentine route, and sprayed alternately horizontally and vertically, and dried after spraying, and the membrane electrode is obtained after drying.
[0059] Specifically, the iridium content of IrO2 powder is 84.5wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 44.8mgIrO2 powder, 149mgNafion solution, 9.3mLn-propanol and 4.7mL deionized water (added in equal amounts twice) are taken and added and mixed in the order of water-IrO2 powder-water-solvent-Nafion solution. The mixed solution is ultrasonically treated for 20 minutes to obtain the IrO2 slurry of the anode.
[0060] The IrO2 slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying, and the spraying was carried out alternately in the horizontal and vertical directions. Finally, different anode catalyst loadings (2.0 mg Ir / cm 2), and after spraying, dry for 30 minutes to obtain the membrane electrode.
[0061] S2: Perform cation exchange treatment on the sprayed membrane electrode, specifically:
[0062] The proton exchange membrane was placed in a 5 wt % NaCl solution and soaked for 12 h to ionize the proton exchange membrane, and then washed with deionized water.
[0063] S3: Heat treatment of the membrane electrode, specifically:
[0064] The membrane electrode treated with cation exchange was placed in an oven at 200° C. and baked for 2 h to obtain a heat-treated membrane electrode.
[0065] S4: Acid treatment is performed on the heat-treated membrane electrode, specifically:
[0066] The heat-treated membrane electrode is placed in a H2SO4 solution (5wt%) and immersed for 4 times to ensure that the membrane electrode is completely protonated. After the immersion treatment is completed, it is rinsed with deionized water and stored.
[0067] Example 3
[0068] The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer provided by the present invention comprises the following steps:
[0069] S1: Coating a catalyst on the surface of a proton exchange membrane, specifically:
[0070] Wherein, step S1 specifically comprises: placing a proton exchange membrane (commercial Nafion 115) on a vacuum heating plate of an ultrasonic spray coating machine, and spraying the catalyst slurry on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0071] S1.1, cathode spraying hydrogen evolution catalyst slurry;
[0072] S1.2, anode spraying of oxygen evolution catalyst slurry.
[0073] Specifically, step S1.1 includes: the cathode hydrogen evolution catalyst slurry includes Pt / C powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spraying machine after ultrasonic mixing, and sprayed in a serpentine route, and sprayed alternately in the horizontal and vertical directions, and dried after the spraying is completed, and turned over after the drying is completed;
[0074] The platinum content of the Pt / C powder is 60wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 8wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 20mg of Pt / C powder, 95.4mg of ionomer solution, 7.2mL of n-propanol and 3.5mL of deionized water are taken, and the mixed solution is subjected to ice bath ultrasonic treatment for 20 minutes to obtain a Pt / C slurry for the cathode.
[0075] The Pt / C slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed in a serpentine route and alternately in the horizontal and vertical directions, and finally the cathode catalyst loading was 0.2mgPt / cm 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0076] Among them, step S1.2 specifically includes: the anode oxygen evolution catalyst slurry includes IrO2 powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spray machine after ultrasonic mixing, sprayed according to a serpentine route, and sprayed alternately horizontally and vertically, and dried after spraying, and the membrane electrode is obtained after drying.
[0077] Specifically, the iridium content of IrO2 powder is 90wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 8wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 60mgIrO2 powder, 180mg Nafion solution, 13.6mL n-propanol and 4.6mL deionized water (added in equal amounts twice) are taken and added and mixed in the order of water-IrO2 powder-water-solvent-Nafion solution. The mixed solution is ultrasonically treated for 20 minutes to obtain the IrO2 slurry of the anode.
[0078] The IrO2 slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying, and the spraying was carried out alternately in the horizontal and vertical directions. Finally, different anode catalyst loadings (2.0 mg Ir / cm 2 ), and after spraying, dry for 30 minutes to obtain the membrane electrode.
[0079] S2: Perform cation exchange treatment on the sprayed membrane electrode, specifically:
[0080] The proton exchange membrane was placed in a 5 wt % NaCl solution and soaked for 15 h to ionize the proton exchange membrane, and then washed with deionized water.
[0081] S3: Heat treatment of the membrane electrode, specifically:
[0082] The membrane electrode treated with cation exchange was placed in an oven at 250° C. and baked for 1 h to obtain a heat-treated membrane electrode.
[0083] S4: Acid treatment is performed on the heat-treated membrane electrode, specifically:
[0084] The heat-treated membrane electrode is placed in a H2SO4 solution (5wt%) and immersed for 4 times to ensure that the membrane electrode is completely protonated. After the immersion treatment is completed, it is rinsed with deionized water and stored.
[0085] Comparative Example 1
[0086] The membrane electrode heat treatment method for changing the ionomer clusters in the catalytic layer provided in this comparative example has the same components and proportions as those in Example 2, and the method steps are basically the same as those in Example 2, except that the steps of the membrane electrode treatment method are changed, and the order of S1, S2, S3, S4 is changed to S2, S3, S4, S1. Specifically:
[0087] The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer provided by the present invention comprises the following steps:
[0088] S1': The proton exchange membrane (commercial Nafion115) is subjected to cation exchange treatment, specifically:
[0089] The proton exchange membrane was placed in a 5wt% NaCl solution and soaked for 12 hours to ionize the proton exchange membrane, and then washed with deionized water;
[0090] S2': heat treating the proton exchange membrane, specifically:
[0091] The proton exchange membrane treated with cation exchange was placed in an oven at 200° C. and baked for 2 hours to obtain a heat-treated proton exchange membrane.
[0092] S3': acid-treating the heat-treated proton exchange membrane, specifically:
[0093] The heat-treated proton exchange membrane is placed in a H2SO4 solution (5wt%) and soaked for 4 times to ensure that the proton exchange membrane is completely protonated. After the soaking treatment is completed, it is rinsed with deionized water and stored.
[0094] S4': Coating a catalyst on the surface of a proton exchange membrane, specifically:
[0095] The step S41' is specifically: placing a proton exchange membrane (commercial Nafion 115) on a vacuum heating plate of an ultrasonic spray coating machine, and spraying the catalyst slurry on the proton exchange membrane by ultrasonic spray coating, which specifically includes the following steps:
[0096] S4.1', cathode spraying hydrogen evolution catalyst slurry;
[0097] S4.2', anode spraying of oxygen evolution catalyst slurry.
[0098] Specifically, step S4.1' comprises: the cathode hydrogen evolution catalyst slurry comprises Pt / C powder, ionomer solution, solvent and water, and after ultrasonic mixing, the slurry is injected into an ultrasonic spraying machine, sprayed in a serpentine route, and sprayed alternately in the horizontal and vertical directions, and dried after the spraying is completed, and turned over after the drying is completed;
[0099] The platinum content of the Pt / C powder is 40wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 17.4mg of Pt / C powder, 70mg of ionomer solution, 3.4mL of n-propanol and 4.6mL of deionized water are taken, and the mixed solution is subjected to ice bath ultrasonic treatment for 20 minutes to obtain a Pt / C slurry for the cathode.
[0100] The Pt / C slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed in a serpentine route and alternately in the horizontal and vertical directions, and finally the cathode catalyst loading was 0.2mgPt / cm 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0101] Specifically, step S4.2' comprises: the anode oxygen evolution catalyst slurry includes IrO2 powder, ionomer solution, solvent and water, and after ultrasonic mixing, the slurry is injected into the ultrasonic spraying machine, sprayed in a serpentine route, and sprayed alternately horizontally and vertically, and dried after spraying, and the membrane electrode is obtained after drying.
[0102] In this embodiment, the iridium content of IrO2 powder is 84.5wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 44.8mg IrO2 powder, 149mg Nafion solution, 9.3mL n-propanol and 4.7mL deionized water (added in equal amounts twice) are taken and added and mixed in the order of water-IrO2 powder-water-n-propanol-Nafion solution. The mixed solution is ultrasonically treated for 20 minutes to obtain the IrO2 slurry of the anode.
[0103] The IrO2 slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying, and the spraying was carried out alternately in the horizontal and vertical directions. Finally, different anode catalyst loadings (2.0 mg Ir / cm 2 ), and after spraying, dry for 30 minutes to obtain the membrane electrode.
[0104] Comparative Example 2
[0105] The membrane electrode heat treatment method for changing the ionomer clusters of the catalytic layer provided in this comparative example has the same components and proportions as those in Example 2, and the method steps are basically the same as those in Example 2, except that step S2 is not performed, and the heat treatment in step S3 is changed to heat treatment at 130° C. for 2 hours, specifically:
[0106] The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer provided by the present invention comprises the following steps:
[0107] S1: Coating a catalyst on the surface of a proton exchange membrane, specifically:
[0108] Wherein, step S1 specifically comprises: placing a proton exchange membrane (commercial Nafion 115) on a vacuum heating plate of an ultrasonic spray coating machine, and spraying the catalyst slurry on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0109] S1.1, cathode spraying hydrogen evolution catalyst slurry;
[0110] S1.2, anode spraying of oxygen evolution catalyst slurry.
[0111] Specifically, step S1.1 includes: the cathode hydrogen evolution catalyst slurry includes Pt / C powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spraying machine after ultrasonic mixing, and sprayed in a serpentine route, and sprayed alternately in the horizontal and vertical directions, and dried after the spraying is completed, and turned over after the drying is completed;
[0112] The platinum content of the Pt / C powder is 40wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 17.4mg of Pt / C powder, 70mg of ionomer solution, 3.4mL of n-propanol and 4.6mL of deionized water are taken, and the mixed solution is subjected to ice bath ultrasonic treatment for 20 minutes to obtain a Pt / C slurry for the cathode.
[0113] The Pt / C slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed in a serpentine route and alternately in the horizontal and vertical directions, and finally the cathode catalyst loading was 0.2mgPt / cm 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0114] Among them, step S1.2 specifically includes: the anode oxygen evolution catalyst slurry includes IrO2 powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spray machine after ultrasonic mixing, sprayed according to a serpentine route, and sprayed alternately horizontally and vertically, and dried after spraying, and the membrane electrode is obtained after drying.
[0115] In this embodiment, the iridium content of IrO2 powder is 84.5wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 44.8mg IrO2 powder, 149mg Nafion solution, 9.3mL n-propanol and 4.7mL deionized water (added in equal amounts twice) are taken and added and mixed in the order of water-IrO2 powder-water-n-propanol-Nafion solution. The mixed solution is ultrasonically treated for 20 minutes to obtain the IrO2 slurry of the anode.
[0116] The IrO2 slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying, and the spraying was carried out alternately in the horizontal and vertical directions. Finally, different anode catalyst loadings (2.0 mg Ir / cm 2 ), and after spraying, dry for 30 minutes to obtain the membrane electrode.
[0117] S2: Heat treatment of the membrane electrode, specifically:
[0118] The sprayed membrane electrode was placed in an oven at 130°C and baked for 2 hours to obtain a heat-treated membrane electrode.
[0119] S3: Performing acid treatment on the membrane electrode after heat treatment, specifically:
[0120] The heat-treated membrane electrode is placed in a H2SO4 solution (5wt%) and immersed for 4 times to ensure that the membrane electrode is completely protonated. After the immersion treatment is completed, it is rinsed with deionized water and stored.
[0121] Comparative Example 3
[0122] The membrane electrode heat treatment method for changing the ionomer clusters in the catalytic layer provided in this comparative example is basically the same as that in Example 2, except that only the ordinary membrane electrode of step S1 is performed, including the following steps:
[0123] S1: Coating a catalyst on the surface of a proton exchange membrane, specifically:
[0124] Wherein, step S1 specifically comprises: placing a proton exchange membrane (commercial Nafion 115) on a vacuum heating plate of an ultrasonic spray coating machine, and spraying the catalyst slurry on the proton exchange membrane by ultrasonic spray coating, specifically comprising the following steps:
[0125] S1.1, cathode spraying hydrogen evolution catalyst slurry;
[0126] S1.2, anode spraying of oxygen evolution catalyst slurry.
[0127] Specifically, step S1.1 includes: the cathode hydrogen evolution catalyst slurry includes Pt / C powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spraying machine after ultrasonic mixing, and sprayed in a serpentine route, and sprayed alternately in the horizontal and vertical directions, and dried after the spraying is completed, and turned over after the drying is completed;
[0128] The platinum content of the Pt / C powder is 40wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 17.4mg of Pt / C powder, 70mg of ionomer solution, 3.4mL of n-propanol and 4.6mL of deionized water are taken, and the mixed solution is subjected to ice bath ultrasonic treatment for 20 minutes to obtain a Pt / C slurry for the cathode.
[0129] The Pt / C slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were: slurry inlet volume 0.3mL / min; ultrasonic power 2.2W; nozzle moving speed 60mm / s; nozzle step distance 3mm; nozzle height 60mm; air inlet pressure 1.5psi; vacuum heating plate 90℃. The catalyst slurry was sprayed in a serpentine route and alternately in the horizontal and vertical directions, and finally the cathode catalyst loading was 0.2mgPt / cm 2 After spraying, dry for 30 minutes and then turn over to spray the anode catalyst layer;
[0130] Among them, step S1.2 specifically includes: the anode oxygen evolution catalyst slurry includes IrO2 powder, ionomer solution, solvent and water, and the slurry is injected into the ultrasonic spray machine after ultrasonic mixing, sprayed according to a serpentine route, and sprayed alternately horizontally and vertically, and dried after spraying, and the membrane electrode is obtained after drying.
[0131] In this embodiment, the iridium content of IrO2 powder is 84.5wt%, the ionomer solution is a solution with a perfluorosulfonic acid resin concentration of 5wt%, the solvent is n-propanol, and the water is deionized water with a resistivity of 18.2MΩcm. 44.8mg IrO2 powder, 149mg Nafion solution, 9.3mL n-propanol and 4.7mL deionized water (added in equal amounts twice) are taken and added and mixed in the order of water-IrO2 powder-water-n-propanol-Nafion solution. The mixed solution is ultrasonically treated for 20 minutes to obtain the IrO2 slurry of the anode.
[0132] The IrO2 slurry was injected into the injection pump of the ultrasonic sprayer. The setting parameters of the ultrasonic sprayer were the same as those for the cathode catalyst layer spraying, and the spraying was carried out alternately in the horizontal and vertical directions. Finally, different anode catalyst loadings (2.0 mg Ir / cm 2 ), and after spraying, dry for 30 minutes to obtain the membrane electrode.
[0133] The membrane electrode heat treatment method for changing the ionomer clusters of the catalytic layer provided by the present invention is applied in hydrogen production by water electrolysis, alkaline water electrolysis, carbon dioxide reduction and fuel cells. The performance is verified by taking the PEM water electrolysis system as an example in the following test.
[0134] Performance Test:
[0135] The present invention performs a performance test on the prepared membrane electrode. This test takes Example 2 as an example, and performs a performance test on the membrane electrodes prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3:
[0136] 1) Morphology test
[0137] The present application uses SEM to perform electron microscope scanning on the membrane electrode obtained after step S1) in Example 2 and the membrane electrode prepared by S1, S2, S3 and S4. The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the pore structure of the membrane electrode changes after heat treatment, and the overall morphology becomes denser.
[0138] 2) Electrochemical performance
[0139] The present application compares the membrane electrode polarization curves obtained by the heat treatment methods of Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively. The results are as follows: Figure 2 In the figure, comparative example 1 is a PEM proton exchange membrane that is heat treated only, and its catalyst layer is not heat treated; comparative example 2 is a membrane electrode that has not undergone step S2 (cation exchange treatment), and at this time the membrane electrode is still H +type; Comparative Example 3 is a membrane electrode that has only undergone step S1 in Implementation 2, and is also the most commonly used membrane electrode at present; the experimental group of Example 2 is a membrane electrode obtained after the heat treatment method of the present invention; commercial PEM proton exchange membranes usually need to be cured at a glass transition temperature (130°C) during the production process to further open the Nafion main chain therein, and step S1 is to spray the catalyst layer at 90°C; in order to eliminate the influence of the heat treatment of the present invention on the PEM proton exchange membrane, the PEM heat treatment control group changes the treatment order (S2, S3, S4, S1) to illustrate that the heat treatment will only affect the agglomeration of the catalyst layer of the membrane electrode, and the specific test results are as follows Figure 2 As shown in the figure, it can be seen that when only the PEM proton exchange membrane is heat treated, the performance is not much different from that of the ordinary membrane electrode, which eliminates the effect of heat treatment on the PEM proton exchange membrane; if the heat treatment is directly performed without the cation exchange treatment in step S2, the performance of the membrane electrode is lower than that of the ordinary membrane electrode; and after the entire membrane electrode is heat treated, the performance is significantly improved under high current density, which shows that the heat treatment mainly affects the catalyst layer ionomer in the membrane electrode.
[0140] 3) Thermal stability test
[0141] This test uses thermogravimetric analysis to test the thermal stability of the membrane electrode prepared by the heat treatment method provided in Example 2 and Comparative Example 2. The specific method steps are: placing the sample in a nitrogen atmosphere, and measuring the weight change process of the sample through a fixed heating program. The results are as follows: Figure 3 As shown in the figure, it can be seen that the mass of the membrane electrode that has not been treated with cation exchange begins to decrease when the temperature reaches 300°C, which is mainly due to the decomposition of the sulfonic acid groups of the Nafion ionomer in the membrane electrode; the mass decreases for the second time at 400°C, which is mainly due to the rupture and decomposition of the PTFE main chain of the Nafion ionomer in the membrane electrode. The mass of the membrane electrode that has been treated with cation exchange begins to decrease at 480°C, which shows that step S2 of the present application: cation exchange treatment can enhance the thermal stability of the membrane electrode.
[0142] In summary, the membrane electrode heat treatment method for changing the catalytic layer ionomer clusters provided by the present invention improves the mobility of the catalytic layer ionomers, improves the coating of the catalyst particles by the ionomers, increases the three-phase interface area of the reaction, and reduces the ohmic loss, thereby improving the overall electrolysis performance.
[0143] The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer provided by the present invention improves the mobility of the main chain and side chain of the ionomer in the catalyst layer to varying degrees by heat treating the membrane electrode, thereby changing the structure of the ionomer clusters in the catalyst layer, reducing the ohmic loss, and improving the overall electrolytic performance of the membrane electrode. When the voltage is 2V, the current density of the membrane electrode after heat treatment is 4A / cm 2 , compared with 3.5A / cm of ordinary membrane electrode 2 It increased by 12.5%, thereby reducing the operating costs of water electrolysis to produce hydrogen and fuel cell operation, and improving overall benefits.
[0144] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A membrane electrode heat treatment method for changing ionomer clusters in a catalyst layer, characterized in that: The steps include: 1) Coating a catalyst on the surface of a proton exchange membrane; 2) Heat treating the membrane electrode obtained in step 1).
2. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 1, characterized in that: The method also includes acid-treating the heat-treated proton exchange membrane.
3. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 1, characterized in that: In step 1), the catalyst is coated on the surface of the proton exchange membrane, specifically: the cathode hydrogen evolution catalyst slurry and the anode hydrogen evolution catalyst slurry are coated on the positive and negative electrodes of the proton exchange membrane respectively.
4. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 3, characterized in that: The cathode hydrogen evolution catalyst slurry comprises Pt / C powder, ionomer solution, solvent and water in a ratio of 15-20 mg: 50-100 mg: 2-8 ml: 3-10 ml.
5. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 4, characterized in that: The platinum content in the Pt / C powder is 20-60wt%, the ionomer is a perfluorosulfonic acid resin with a mass concentration of 3-8%, the solvent is n-propanol, and the water is deionized water.
6. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 3, characterized in that: The anode hydrogen evolution catalyst slurry comprises IrO2 powder, ionomer solution, solvent and water in a ratio of 30-60 mg: 120-180 mg: 5-15 ml: 2-8 ml.
7. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 6, characterized in that: The iridium content in the IrO2 powder is 70-90wt%, the ionomer is a perfluorosulfonic acid resin with a mass concentration of 3-8%, the solvent is n-propanol, and the water is deionized water.
8. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 2, characterized in that: It also includes performing cation exchange treatment on the membrane electrode before heat treating the membrane electrode; and the cation exchange treatment specifically includes: placing the proton exchange membrane in a cation-containing aqueous solution and soaking it for 10-15 hours, and then washing it with deionized water.
9. The membrane electrode heat treatment method for changing the ionomer clusters in the catalyst layer according to claim 1, characterized in that: The heat treatment conditions in step 2) are: heat treatment temperature is 150-250° C., and heat treatment time is 1-3 h.
10. Use of a membrane electrode heat treatment method for changing ionomer clusters in a catalytic layer according to any one of claims 1 to 9 in hydrogen production by water electrolysis, alkaline water electrolysis, carbon dioxide reduction and fuel cells.
Citation Information
Patent Citations
Method for preparing membrane electrode for hydrophilicity and hydrophobicity-adjustable proton exchange membrane fuel battery on the basis of catalyst / membrane technology
CN101800321A
Integrated preparation method for membrane-membrane electrode for fuel cell
CN101887975A
Preparation method and application of ion exchange Nafion-based membrane electrode
CN114843565A
Membrane electrode of proton exchange membrane fuel cell and preparation method of membrane electrode
CN117059849A
Pretreatment method and application of membrane electrode
CN117107260A
Cited By
Modified ionomer, modification method thereof and application of modified ionomer in membrane electrode
CN119684506A
Proton exchange membrane electrolyzed water membrane electrode with catalyst layer constructed by mixed ionomers and preparation method of proton exchange membrane electrolyzed water membrane electrode
CN120006312A
A proton exchange membrane water electrolysis membrane electrode with a mixed ionomer constructed catalytic layer and a preparation method thereof
CN120006312B
Post-treatment method of carbon-supported platinum-based catalyst
CN120033264A
Preparation method of catalyst layer and membrane electrode
CN122214900A
